Human Apoptotic Cells, Generated by Extracorporeal Photopheresis, Modulate Allogeneic Immune Response - Pilon, Caroline; Stehlé, Thomas; Beldi-Ferchiou, Asma; Matignon, Marie; Thiolat, Allan; Burlion, Aude; Grondin, Cynthia; Birebent, Brigitte; Pirenne, France; Rouard, Hélène; Lang, Philippe; Marodon, Gilles; et al. (Frontiers in Immunology, 2019)
The induction of specific and sustainable tolerance is a challenging issue in organ transplantation. The discovery of the immunosuppressive properties of apoptotic cells in animal models has paved the way for their use in human transplantation. In this work, we aimed to define a stable, reproducible, and clinically compatible production procedure of human apoptotic cells (Apo-cells). Using a clinically approved extracorporeal photopheresis technique, we have produced and characterized phenotypically and functionally human apoptotic cells. These Apo-cells have immunosuppressive properties proved in vitro and in vivo in NOD/SCID/γC mice by their capacity to modulate an allogeneic response following both a direct and an indirect antigen presentation. These results brought the rationale for the use of Apo-cells in tolerance induction protocol for organ transplantation.